Political Attitudes of Arab Citizens in North Africa - Rahbarqazi, Mahmoudreza; Emamjomehzadeh, Seyed Javad; Masoudnia, Hossein (Politologija, 2019)
Theories of social capital, government performance, Islamic values, and globalization are among the most important tools that can be used to help explain individuals’ political attitudes. The present research attempts to address the effects of the abovementioned factors on the political attitude of Arab citizens using the Arab Barometer Wave IV data. The results showed that only 23.2% of citizens disagreed with a democratic political system, while 70.3% and 60.1% expressed their opposition to authoritarian and Shari’ah-based systems. Results of the final model of research indicated that memberships in social associations, on the one hand, increased the tendency of individuals to support authoritarian and law-based political systems and, on the other hand, did not have any significant effect on the tendency toward supporting a democratic political system. It was concluded that improving economic performance not only affected the promotion of the Shari’ah-based political system, but that Political Performance also reduced the inclinations toward Shari’ah and authoritarianism. Furthermore, Political Performance increased the tendency of individuals to favor a democratic system. In addition, although individuals’ support for a Shari’ah-based political system had increased, Islamic values did not act as a barrier that would keep individuals away from favoring a democratic political system. Among the variables of globalization, the expansion of communication reduced people’s tendencies toward Shari’ah and authoritative political systems, along with a positive effect on strengthening support for democratic systems. Ultimately, Westernization only affected the shrinking support of some Shari’ah-based political systems.
Keywords: Social Capital; Government Performance; Islamic Values; Globalization; Political Systems